KRITERIA INGKAR JANJI PADA PEMBIAYAAN MUSYARAKAH DI BANK SYARIAH (Lex Journal: Kajian Hukum & Keadilan, 2018)
Musyarakah is a cooperation contract between two or more parties for a particular business that each party provides a portion of the fund provided that the profit will be divided according to the agreement, while the loss will be borne in accordance with the respective portion of the fund. When a customer does not provide a profit sharing ratio, it is categorized as a broken promise. So the problem that will be analyzed is that the customer criteria are said to breach of contract to musyarakah financing. The approach used in this study is the legislative, conceptual and case approach. The criteria of breach of contract for musyarakah financing when the customer does not have good intentions in carrying out payment according to the agreed time period or the customer does not carry out payment of principal and profit sharing ratio while the business is still running so that there is still income earned by the customer. Then the customer is obliged to fulfill it in accordance with a contract that has been mutually agreed upon.Keywords: breach of contract, musyarakah, sharia bank